HUBUNGAN ANTARA KUALITAS PELAYANAN DAN PERSONAL SELLING DENGAN KEPUASAN NASABAH BANK MANDIRI CABANG CISARUA - Purnama, Denta; Muharam, Hari; Horas V Purba, Jan (Economicus, 2018)
The research objectives to be achieved based on the problems above are to find out the relationship between service quality and personal selling with the satisfaction of micro credit customers. And the contribution of service quality variables (X1) to customer satisfaction (Y) obtained R Square (R²) value of 0.615, This means that service quality (X1) forms a contribution of 61.5% to customer satisfaction (Y). There is a positive and significant relationship between the variable personal selling and customer satisfaction with the value of the correlation coefficient (r) of 0.765 which means strong. And the contribution of personelling variable (X2) to customer satisfaction (Y) obtained R Square value of 0.585, This means that the personal selling variable (X2) forms a contribution of 58.5% to customer satisfaction (Y). There is a positive and significant relationship variable service quality and personal selling together with customer satisfaction with the value of the correlation coefficient (r) of 0.786 which means that it is strong enough. And the contribution of service quality (X1) and personal selling (X2) together on customer satisfaction (Y) obtained an Adjusted R Square (R²) value of 0.611.